(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The purpose of this work is to analyze Iberian inscriptions from Empúries by means of their relationship with contemporary Greek and Latin inscriptions. The exact correlation between suports, technics and scripturary functions brings to consider the epigraphical fact as a unitary phenomenon which found expression in three different languages.